Digital tools in allergy and respiratory care - Verhoeven, Elisabeth; Rouadi, Philip; Jaoude, Eliane Abou; Abouzakouk, Mohamed; Ansotegui, Ignacio; Al-Ahmad, Mona; Al-Nesf, Maryam Ali; Azar, Cecilio; Bahna, Sami; Cuervo-Pardo, Lyda; Diamant, Zuzana; Douagui, Habib; et al. (The World Allergy Organization journal, 2022)
Patient care in the allergy and respiratory fields is advancing rapidly, offering the possibility of the inclusion of a variety of digital tools that aim to improve outcomes of care. Impaired access to several health care facilities during the COVID-19 pandemic has considerably increased the appetite and need for the inclusion of e-health tools amongst end-users. Consequently, a multitude of different e-health tools have been launched worldwide with various registration and access options, and with a wide range of offered benefits. From the perspective of both patients and healthcare providers (HCPs), as well as from a legal and device-related perspective, several features are important for the acceptance, effectiveness,and long-term use of e-health tools. Patients and physicians have different needs and expectations of how digital tools might be of help in the care pathway. There is a need for standardization by defining quality assurance criteria. Therefore, the Upper Airway Diseases Committee of the World Allergy Organization (WAO) has taken the initiative to define and propose criteria for quality, appeal, and applicability of e-health tools in the allergy and respiratory care fields from a patient, clinician, and academic perspective with the ultimate aim to improve patient health and outcomes of care.